Association of IL-17A gene polymorphism rs2275913 with the polycystic ovary syndrome in Yunnan Province, China. (April 2022) - Zou, Li; Cheng, Yun; Yang, Linna; Zhang, Fen; Zhao, Han; Nian, Lei; Li, Yulan; Feng, Yun
Abstract: Objective: Polycystic ovary syndrome (PCOS) is a reproductive system disease with high incidence in women of childbearing age. However, the cause and risk factor are not clear. Our study aims to explore whether IL-17A gene polymorphism rs2275913 is associated with the PCOS in women from Yunnan province, China. Materials and methods: From January 2018 to December 2020, we collected 287 specimens from PCOS patients and 279 specimens from healthy women. The rs2275913 in the IL-17A promoter region were detected by PCR-Sanger sequencing. Detailed clinical symptoms were recorded and hormone levels were measured on all enrolled individuals. The risk of rs2275913 to PCOS was evaluated by using a multivariate logistic regression model. Results: The distribution of rs2275913 in the control group and the PCOS group was statistically different. The multivariate logistic regression model showed that rs2275913 could increase the risk of PCOS occurrence. Among PCOS patients, patients carrying rs2275913 A allele increased serum IL-17A levels and could lead to more disturbed hormone levels and have a bit severe clinical manifestation. Conclusion: This case-control study proves that the rs2275913 is a risk factor for the occurrence of PCOS.